Intravenous Administration of Pyroglutamyl Apelin-13 Alleviates Murine Inflammatory Pain via the Kappa Opioid Receptor - Lv, Shuangyu; Zhang, Xiaomei; Feng, Yu; Zhou, Yuchen; Cui, Binbin; Yang, Yanjie; Wang, Xinchun (Frontiers in Neuroscience, 2020)
Apelin is an endogenous neuropeptide, which has wide distribution in central nervous system and peripheral tissues. Pyroglutamyl apelin-13 [(pyr)apelin-13] is the major apelin isoform in human plasma. However, the role of peripheral (pyr)apelin-13 in pain regulation is unknown. The aim of this study was to investigate the effect of the peripheral injection of (pyr)apelin-13 on inflammatory pain using the formalin test, and as well as to evaluate the mechanistic basis for the effect. Results showed intravenous (i.v.) injection of (pyr)apelin-13 (10, 20 mg/kg) to significantly decrease licking/biting time during the second phase of the mouse formalin test. In contrast, i.v. injection of apelin-13 had no influence on such effect. Intramuscular injection of (pyr)apelin-13 reduced licking/biting time during the second phase only at a dose of 20 mg/kg. The antinociception of i.v. (pyr)apelin-13 was antagonized by the apelin receptor (APJ, angiotensin II receptor-like 1) antagonist, apelin-13(F13A). (pyr)apelin-13 (i.v. 20 mg/kg) markedly up-regulated Aplnr and Adcy2 gene expression in the prefrontal cortex, while Fos gene expression was down-regulated. The antinociception of i.v. (pyr)apelin-13 was blocked by the opioid receptor antagonist naloxone and the specific kappa opioid receptor (KOR) antagonist nor-binaltorphimine (nor-BNI). (pyr)apelin-13 up-regulated the dynorphin and KOR gene expression and protein levels in the mouse prefrontal cortex, not in striatum. (pyr)apelin-13 did not influence the motor behavior. Our results demonstrate that i.v. injection of (pyr)apelin-13 to induce antinociception via the KOR in the inflammatory pain mouse model.